Antibacterial activity of sea hare (Dolabella auricularia) egg string extracts against potentially pathogenic bacteria - CHENCY GRACE O. LIGUEZ; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Liguez CGO, Tabugo SR. 2023. Antibacterial activity of sea hare (Dolabella auricularia) egg string extracts against potentially pathogenic bacteria. Biodiversitas 24: 6675-6683. Pharmaceutical industries now recognize the vast variety of ocean organisms, each possessing distinct biological characteristics. Sea hares, for example, are marine organisms that use bioactive chemicals to defend against predators, including their eggs. To explore the potential antibacterial properties of sea hare species (Dolabella auricularia) found in Pujada Bay, Philippines, egg strings were collected and extracted using hexane and methanol solvents. The antibacterial activity of each fraction was then determined through Minimum Inhibitory Concentration (MIC) testing against four potentially pathogenic bacteria, two gram-positive strains (Staphylococcus aureus, Bacillus subtilis) and two gram-negative strains (Escherichia coli, Pseudomonas aeruginosa). The broth microdilution method was employed to assess the antibacterial activity of Dolabella auricularia egg strings. The results revealed the MIC values for the four bacterial strains. The hexane extracts of both extract 1 and extract 2 exhibited a MIC of 0. 23 and 0.33 mg/mL and a MIC of 0.52 and 0.125 mg/mL against P. aeruginosa, respectively. The methanolic extracts (1 and 2) displayed a MIC of 1.46 and 2.83 mg/mL against E. coli and an even more potent MIC of 1.33 and 0.79 mg/mL against P. aeruginosa. In the case of B. subtilis, the hexane extracts (1 and 2) had a MIC of 1.5 and 0.54 mg/mL, while the methanolic extracts (1 and 2) exhibited a MIC of 1.17 mg/mL and 0.83 mg/mL. Lastly, against S. aureus, hexane extracts (1 and 2) suppressed the growth with a MIC of 0.77 mg/mL and 0.25 mg/mL, respectively, while both methanolic extracts (1 and 2) demonstrated a MIC of 3.33 mg/mL. These findings showcase the promising antibacterial activity of Dolabella auricularia egg string extracts and highlight their potential for further investigation and development in the pharmaceutical field.